Mesenchymal stem cell-derived extracellular vesicles for treatment of bone loss within periodontitis in pre-clinical animal models: a meta-analysis - Huan Zhou; Yan-Xin Qi; Chun-Hui Zhu; Ang Li; Dan-Dan Pei (BMC, 2023)
Abstract Background Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) represent an effective and promising strategy for periodontitis, although studies remain pre-clinical. Herein, a meta-analysis was conducted to assess the efficacy of MSC-EVs in animal models of periodontitis. Methods The PubMed, Web of Science, and Embase electronic databases were searched up to Dec 2022 to retrieve preclinical studies examining the use of MSC-EVs for periodontitis treatment. Meta-analyses and sub-group analyses were performed to assess the effect of MSC-EVs on Bone Volume/Total Volume (BV/TV) or the distance between the cementoenamel junction and alveolar bone crest (CEJ-ABC) in pre-clinical animal models of periodontitis. Results 11 studies published from Mar 2019 to Oct 2022 met the inclusion criteria. Overall, MSC-EVs contributed to periodontal bone regeneration in the inflammatory bone loss area due to periodontitis, as represented by a weighted mean difference (WMD) of 14.07% (95% CI = 6.73, 21.41%, p < 0.001) for BV/TV and a WMD of -0.12 mm (95% CI= -0.14, -0.11 mm, p < 0.001) for CEJ-ABC. However, sub-analysis suggested that there was no significant difference in CEJ-ABC between studies with bioactive scaffolds and studies without bioactive scaffolds (p = 0.60). Conclusions The present study suggests that MSC-EVs may represent an attractive therapy for the treatment of inflammatory bone loss within periodontitis.